Microtomographic investigation of a large corpus of cichlids. - David Haberthür; Mikki Law; Kassandra Ford; Marcel Häsler; Ole Seehausen; Ruslan Hlushchuk (PLoS ONE, 2023)
A large collection of cichlids (N = 133) from Lake Victoria in Africa, with total lengths ranging from 6 to 18 cm was nondestructively imaged using micro-computed tomography. We present a method to efficiently obtain three-dimensional tomographic datasets of the oral and pharyngeal jaws and the whole skull of these fishes to accurately describe their morphology. The tomographic data we acquired (9.8 TB of projection images) yielded 1.5 TB of three-dimensional image stacks used for extracting the relevant features of interest. Herein we present our method and outlooks on analyzing the acquired data; a morphological description of the oral and pharyngeal jaws, a three-dimensional geometric morphometrics analysis of landmarked skull features, and a robust method to automatically extract otoliths from the tomographic data.